2022
DOI: 10.1215/00703370-9656369
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Horizontal Stratification in Higher Education: College Prestige Hierarchy and Educational Assortative Mating in China

Abstract: Existing research on assortative mating has examined marriage between people with different levels of education, yet heterogeneity in educational assortative mating outcomes of college graduates has been mostly ignored. Using data from the 2010 Chinese Family Panel Study and log-multiplicative models, this study examines the changing structure and association of husbands' and wives' educational attainment between 1980 and 2010, a period in which Chinese higher education experienced rapid expansion and stratifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…We used a cross-sectional survey method to collect data from university students. In general, under China's key university system, differences have been noted in the mental health changes experienced by students attending key and regular universities (Xin et al, 2012;Feng, 2022). We were aware that this may lead to a difference in the prevalence of academic burnout among students at these different types of universities.…”
Section: Participants and Proceduresmentioning
confidence: 93%
“…We used a cross-sectional survey method to collect data from university students. In general, under China's key university system, differences have been noted in the mental health changes experienced by students attending key and regular universities (Xin et al, 2012;Feng, 2022). We were aware that this may lead to a difference in the prevalence of academic burnout among students at these different types of universities.…”
Section: Participants and Proceduresmentioning
confidence: 93%
“…For instance, Billédi (1989, p. 328) defines prestige as "the respect of someone's knowledge, expertise or possession of specially valued talents" in the context of occupational prestige. Other scholars studied linguistic prestige (social prestige of a language) (O 'Donnell, 1988), brand prestige (Tuškej & Podnar, 2018), higher education prestige (Feng, 2022). Prestige is related to success since it can signify that an individual is successful, that an individual possesses certain prestigious belongings or has certain personal qualities that are socially respectable.…”
Section: Conceptualizationsmentioning
confidence: 99%
“…The dis tinc tion between expan sion and dif fer en ti a tion pro vi des impor tant insights, espe cially when the growth of less selec tive insti tu tions pro motes an increase in the num ber of peo ple with higher edu ca tion (Arum et al 2007:5). Although they only indi rectly addressed the topic, a few stud ies have found that col lege selec tiv ity is asso ci ated with mar ry ing spouses from post sec ond ary insti tu tions with sim i lar aca demic selec tiv ity (Arum et al 2008;Feng 2022;Uchikoshi and Raymo 2021). These results sug gest that grad u ates of selec tive insti tu tions are more likely to seek mar riage part ners who are col lege grad u ates of sim i larly ranked insti tu tions to main tain social bound aries, which is con sis tent with the exclu siv ity hypoth e sis.…”
Section: Expansion and Differentiation In Higher Education Institutionsmentioning
confidence: 99%